2015
DOI: 10.1589/jpts.27.1191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body awareness training on mild visuospatial neglect in patients with acute stroke: a pilot randomized controlled trial

Abstract: [Purpose] This study aimed to investigate the effects of body awareness training (BAT) on mild visuospatial neglect in patients following acute stroke. [Subjects] The subjects were 12 stroke patients randomly assigned to either the experimental group (n1=6) or control group (n2=6). [Methods] The experimental group underwent BAT for 15 minutes and then task-oriented training for 30 minutes a day, five times a week for three weeks. The control group underwent task-oriented training for 30 minutes a day, five tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…This study investigated the effect of mental practice on unilateral neglect of patients with stroke. The results of this study indicate that the mental practice may have therapeutic benefits for unilateral neglect and is consistent with the results of previous studies 10 , 18 , 19 ) .…”
Section: Discussionsupporting
confidence: 92%
“…This study investigated the effect of mental practice on unilateral neglect of patients with stroke. The results of this study indicate that the mental practice may have therapeutic benefits for unilateral neglect and is consistent with the results of previous studies 10 , 18 , 19 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Previously, it was demonstrated that gravitational inputs could modulate unilateral spatial neglect (26). In addition, body awareness induced by training has been shown to be an effective method in the treatment of visuospatial neglect (27). The balance platform enhances postural control system of the body by giving feedback to the patient this limited inclusion of all stroke patients with UN.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with stroke often show asymmetric standing balance, which affects stability limits, and can cause difficulty in recovery of functional independence 3 ) . Impaired postural control ability is a barrier to improvement of balance and walking ability for independent living in patients with damage to the central nervous system 4 ) . Gait disruption not only limits independent living for stroke patients, but also puts them at risk for fall-related injuries and for development of secondary impairments 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that BAT could be beneficial for improving balance in stroke patients 4 ) . However, there are no reported studies on the effects of BAT on balance and walking ability in chronic stroke patients.…”
Section: Introductionmentioning
confidence: 99%